Integrative Bioinformatics Reveals the Lactate Dehydrogenase B (LDHB) Significance in Colon Adenocarcinoma - Wulandari, Febri; Hanifa, Mila (Cell and BioPharmaceutical Institute, 2023)
Background: Lactate dehydrogenase B (LDHB), a typical oxidoreductase for converting lactate to pyruvate in the glycolysis process, takes a complex function in the progression of cancer cells. Even so, the profile of LDHB relevance in colon adenocarcinoma (COAD) remains ambiguous. Hence this study analyzed the expression and co-expression profile of LDHB, and its immune correlation in COAD.Materials and method: The mRNA expression and co-expression of LDHB in COAD were retrieved from UALCAN. The immune infiltration levels of LDHB from B cells, CD4+ T cells, CD8+ T cells, macrophages, neutrophils, and dendritic cells in COAD were assessed using the TIMER database. For assessing gene ontology and the KEGG pathway, DAVID v6.8 was utilized. The protein-protein interaction of LDHB-correlated genes was analyzed using STRINGDB and Cytoscape.Results: Significantly high expression of LDHB in COAD was spotted in several sample types and associated with a poor overall survival rate. Further, LDHB corresponded to the level of CD4+, macrophages, and myeloid-derived suppressor cell (MDSC) immune infiltrating cells. The co-expression of LDHB was associated with several essential genes for cell cycle progression.Conclusion: The findings of this study indicate an upcoming involvement of LDHB in COAD tumorigenesis and prognosis. Additionally, this study highlights the immune correlation of LDHB in COAD as preliminary data in developing diagnosis and treatment with a novel immune checkpoint in COAD.Keywords: lactate dehydrogenase, colon adenocarcinoma, expression, survival, immune